2015
DOI: 10.1523/jneurosci.0106-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Phase Difference Between Neural Drives to Antagonist Muscles in Essential Tremor Is Associated with the Relative Strength of Supraspinal and Afferent Input

Abstract: The pathophysiology of essential tremor (ET), the most common movement disorder, is not fully understood. We investigated which factors determine the variability in the phase difference between neural drives to antagonist muscles, a long-standing observation yet unexplained. We used a computational model to simulate the effects of different levels of voluntary and tremulous synaptic input to antagonistic motoneuron pools on the tremor. We compared these simulations to data from 11 human ET patients. In both an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 112 publications
0
60
0
Order By: Relevance
“…This lowfrequency input is the most commonly used in previous simulation studies (Farina et al, 2014;Gallego et al, 2015) of muscle force control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lowfrequency input is the most commonly used in previous simulation studies (Farina et al, 2014;Gallego et al, 2015) of muscle force control.…”
Section: Methodsmentioning
confidence: 99%
“…Due to unsurmountable experimental difficulties to measure the inputs to MN pools in humans (Heckman and Enoka, 2012), the study of how the CSIs influence the MN spike trains was approached previously by means of computer model simulations (Williams and Baker, 2009a,b;Stegeman et al, 2010;Negro andFarina, 2011a,b, 2012;Watanabe et al, 2013;Farina et al, 2014;Gallego et al, 2015). This approach was also used to study oscillatory CSIs in general neuron populations (Knight, 1972;Fourcaud-trocme et al, 2003) (MNs and MUs).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions between muscles are also yet not fully understood. For example, it has been recently demonstrated that not all the muscles are equally affected by ET [20] and that the interaction between antagonist muscles is different across conditions and patients, and intrinsically nonstationary [21].…”
Section: Complexitymentioning
confidence: 99%
“…However, not all of these algorithms are applicable to hdEMG data in pathological tremor; in pathological tremor, motor unit firings tend to be significantly more synchronized than in healthy conditions [21,23], causing bursts of EMG activity ( Figure 2) that are very difficult to decompose into the contributions of individual motor units. The Convolution Kernel Compensation (CKC) technique has been recently demonstrated to successfully solve this problem [23], providing a solid ground for fully automatic and highly accurate assessment of the tremulous neural drive to muscles.…”
Section: Neural Drive To Skeletal Muscles and Tremor Demonstration Inmentioning
confidence: 99%
“…As in previous studies of motor unit activity in tremor [32], only identified spike trains with pulse-to-noise ratio ^26 dB (metric describing the decomposition accuracy; see [33] for details) was included in the analysis. For each muscle pair, a period of 30 s of the complete recording was selected for further analysis.…”
Section: Experimental Data Analysismentioning
confidence: 99%